THE ROLE OF FINANCIAL RISKS IN ASSESSING AND OPTIMIZING THE IMPACT OF GOVERNMENT SPENDING ON ECONOMIC GROWTH - Khurshidbek Kurbonaliev, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This thesis examines, from a theoretical perspective, how financial risks  shape  the  assessment  and  optimization  of  government  spending's  effect  on economic growth in developing countries. It argues that while public expenditure on infrastructure,  health,  and  education  can  raise  both  short-run demand  and  long-run productive capacity, three financial risks debt sustainability, inflation, and contingent liabilities substantially condition the size and direction of fiscal multipliers. High and growing public debt narrows fiscal space, raises borrowing costs, and can reduce or reverse  the  growth  impact  of  additional  spending.  Inflation,  whether  driven  by monetary financing or capacity constraints, erodes the real value and effectiveness of public investment and raises uncertainty for private investors. Contingent liabilities (guarantees, bailouts, PPP commitments) represent hidden fiscal exposures that can abruptly raise public debt and crowd out development spending. The thesis synthesizes theoretical  frameworks  (Keynesian  demand  management  and  endogenous  growth models) with institutional guidance from the IMF and World Bank (Debt Sustainability Framework and fiscal-risk best practices), and concludes that optimizing fiscal policy in  developing  economies  requires  careful  composition  of  spending,  medium-term fiscal frameworks, explicit fiscal risk management, and strong institutions to preserve both growth and macro-financial stability.